Acrodermatitis Enteropathica A Clinician's Guide - Khan Mohammad Beigi, Pooya; Maverakis, Emanual (Springer International Publishing : Imprint: Springer, 2015)
Written by and for dermatologists, pediatric and obstetrics specialists. This book presents the groundbreaking work of Dr. Pooya Khan Mohammad Beigi M.D., whose clinical research study on Acrodermatitis Enteropathica (AE) is the largest ever conducted on this rare disorder. The only book of its kind to offer insights into AE, it not only includes dozens of high quality photographs, illustrations, and clinical tables, but also covers everything from the history of AE to categories of the disorder, molecular analysis, epidemiology, disorder signs and symptoms, diagnosis, treatment, and more. Acrodermatitis Enteropathica is a rare disorder of zinc metabolism that occurs in one of two forms: inborn and acquired. If untreated, this disease is fatal and affected individuals may die within just a few years. Therefore, it is critical that physicians are aware of the signs and symptoms related to AE and the appropriate treatments available for patients.